Browse's introduction to the symptoms & signs of surgical disease - Burnand, Kevin G.; Diagnosis, Surgical (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2015)
The fifth edition of this essential textbook has been fully revised and updated to ensure it continues to meet the needs of all those learning the principles of surgical examination
History-taking and clinical examination / Kevin G. Burnand, Norman L Browse -- The heart, lungs, and pleura / Timothy JP Batchelor -- The brain, central nervous system, and peripheral nerves / Peter Bullock -- The skin and subcutaneous tissues / Pari-Naz Mohanna, Samer Saour -- The symptoms, signs, and emergency management of major injuries / Tom Carrell -- Bones, joints, muscles and tendons / Steven A. Corbett, Kevin G Burnand -- Upper limb symptoms and signs / Steven A Corbett -- Lower limb symptoms and signs / Jay D Smith, Diane L. Back, Sam Singh, Jay D. Smith -- The spine and pelvis / Jonathan Lucas -- The arteries, veins and Lymphatics / Kevin G. Bernand, Bijan Modarai -- The mouth, tongue, and lips / Mark McGurck, Leandros-Vassilios Vassiliou -- The neck / William EG Thomas -- The breast / John Black -- The breast / John Black -- History and examination of breast disease -- The abdominal wall, hernias, and the umbilicus / Matthew Bultitude, John Black -- The abdomen / James A. Gossage, Kevin G. Burnand -- The rectum and anal canal / Ruth McKee -- The kidney, urinary tract, and prostate / Matthew Bultitude, Ben Challacombe -- The external genitalia / Matthew Bultitude, Ben Challacombe
Includes index
Keywords: Diagnostic Techniques, Surgical; History-taking and clinical examination / Kevin G. Burnand, Norman L Browse -- The heart, lungs, and pleura / Timothy JP Batchelor -- The brain, central nervous system, and peripheral nerves / Peter Bullock -- The skin and subcutaneous tissues / Pari-Naz Mohanna, Samer Saour -- The symptoms, signs, and emergency management of major injuries / Tom Carrell -- Bones, joints, muscles and tendons / Steven A. Corbett, Kevin G Burnand -- Upper limb symptoms and signs / Steven A Corbett -- Lower limb symptoms and signs / Jay D Smith, Diane L. Back, Sam Singh, Jay D. Smith -- The spine and pelvis / Jonathan Lucas -- The arteries, veins and Lymphatics / Kevin G. Bernand, Bijan Modarai -- The mouth, tongue, and lips / Mark McGurck, Leandros-Vassilios Vassiliou -- The neck / William EG Thomas -- The breast / John Black -- The breast / John Black -- History and examination of breast disease -- The abdominal wall, hernias, and the umbilicus / Matthew Bultitude, John Black -- The abdomen / James A. Gossage, Kevin G. Burnand -- The rectum and anal canal / Ruth McKee -- The kidney, urinary tract, and prostate / Matthew Bultitude, Ben Challacombe -- The external genitalia / Matthew Bultitude, Ben Challacombe; The fifth edition of this essential textbook has been fully revised and updated to ensure it continues to meet the needs of all those learning the principles of surgical examination